2020
DOI: 10.1002/ajhb.23499
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and gender minority health vulnerabilities during the COVID‐19 health crisis

Abstract: Coronavirus 19 (COVID-19), the infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is both transforming and ending lives. In only 7 months (December 2019-July 2020), at least 11 million people have contracted the virus and over 500 000 have died (WHO, 2020). Though its impact is wide, COVID-19's illness and death tolls are felt most acutely by communities experiencing multiple and inter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 83 publications
1
100
0
2
Order By: Relevance
“…These individuals may even become involved in practices in which they expose themselves to the Coronavirus for not bearing the prolonged social distancing measures, boredom, and the lack of social interaction with people, or restricted mobility within the cities (Reis de Sousa et al, 2020). Coupled with these is the fact that difficulty in searching for affective and sexual partners during the period of social isolation may also decrease psychological well-being, impacting the health of these men (Sousa & Oliveira et al, 2020; Carvalho et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These individuals may even become involved in practices in which they expose themselves to the Coronavirus for not bearing the prolonged social distancing measures, boredom, and the lack of social interaction with people, or restricted mobility within the cities (Reis de Sousa et al, 2020). Coupled with these is the fact that difficulty in searching for affective and sexual partners during the period of social isolation may also decrease psychological well-being, impacting the health of these men (Sousa & Oliveira et al, 2020; Carvalho et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a greater prevalence of low psychological well-being was found among MSM who did not report the use of social media to find partners, revealing that even though the social media is considered to be associated with sex, in times of social distancing, it may play a protective role by enabling social interactions, even if remotely. The results from a multi-center study show that 95% of its MSM sample was (totally or partially) complying with social distancing measures, which resulted in a drop in the number of partners and relationships, but, at the same time, increased online interactions (Sousa & Oliveira et al, 2020). The study also reports that MSM devised strategies to keep interactions during the social distancing measures, reinforcing this study’s findings that interactions, whether to seek or exchange content, are essential for MSM’s psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the complexity of addressing these issues of measurement and inclusivity, transdisciplinary collaborations can enable the most comprehensive use of current and future sexual orientation and gender identity measures. Inclusion of these measures would facilitate researchers' capacity to effectively disentangle intersectional factors impacting health and development across the life span beyond WEIRD populations (Bauer & Scheim, 2019a; Gibb et al, 2020).…”
Section: Identifying and Meeting Challengesmentioning
confidence: 99%